Análisis estático de un pórtico plano de baja altura por el método de la rigidez - Guillen Ramirez, Bryan Daniel (My University, 2019)
An analytical methodology of an exploratory nature is applied to settle the criteria related to the structural calculation, arguing the resolution of the practical case through iterative modeling in the development of the portico, in contrast to the aforementioned bibliographic review; The subject is also approached in a contextual way to determine its status at an international, national and local level, highlighting the vanguard technologies or processes linked to structural study. In the final part, the process performed in the calculation is outlined, explains the use of the formulations, equations and inferences related to the problem posed, and also presents the values obtained synthesized by means of a table; in the conclusions the explanations of the author are postulated, from the epistemological point of view to explain his mastery of the subject.
Se aplica una metodología analítica, de carácter exploratoria para dirimir los criterios afines al cálculo estructural, argumentando la resolución del caso práctico a través de la modelación iterativa en el desarrollo del pórtico, en contraste con la revisión bibliográfica citada; también se aborda la temática en forma contextual para determinar su estado a nivel internacional, nacional y local, destacando las tecnologías o procesos de vanguardia vinculados al estudio estructural. En la parte final se esquematiza el proceso ejecutado en el cálculo, explica el uso de las formulaciones, ecuaciones e inferencias relacionadas a la problemática planteada, también se presentan los valores obtenidos sintetizados por medio de una tabla; en las conclusiones se postulan las explicaciones del autor, desde el punto de vista epistemológico para explicar su dominio del tema.he relevant documentation describes the detailed process for calculating a flat gantry, using the rigidities method to determine the stresses and displacements in its elements.
Keywords: CÁLCULO ESTRUCTURAL; PÓRTICO PLANO